Sexual Abuse against Children by Islamic Boarding School Authorities in Lamongan: A Critical Discourse Analysis - Rifqiyah Humaidah; Rahayu, Wulan Sri; Kezya Agitha; Balqis Tsani; Vidia Ali Syaharani; Listyani, Refti Handini (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2026)
This study examines cases of violence, particularly sexual abuse of children, perpetrated by authorities in Islamic boarding schools in Lamongan, as represented in INews media coverage. The study employs a qualitative descriptive approach and draws on Teun A. van Dijk’s model of critical discourse analysis, which encompasses three dimensions: textual analysis, social cognition, and social context. The textual analysis focuses on the macrostructure, superstructure, and microstructure of the news discourse to identify dominant themes and narrative patterns. The findings indicate that the reports not only present factual information regarding the perpetrator’s arrest but also construct a broader discourse on the abuse of power by religious authorities. At the macrostructural level, the coverage foregrounds themes of criminality within religious institutions. At the superstructural level, the narrative is systematically organized, moving from case introduction to public reaction. At the microstructural level, the discourse employs assertive diction and an emotionally charged style to emphasize the gravity of the case. In terms of social cognition, the news discourse reflects a journalistic stance aligned with law enforcement and the protection of victims. Within the dimension of social context, the discourse reveals unequal power relations, in which the perpetrator occupies a dominant position while the victims are placed in vulnerable conditions. The INews coverage contributes to raising public awareness and encourages firm responses to sexual abuse within religious-based educational institutions.